Effectiveness of Plant Adaptogens in Sports: Bibliometric Study and Prospects for Use - Igor V. Goncharenko; Viktoriia A. Pastukhova; Halyna V. Lukyantseva (Traditional and Integrative Medicine)
Rehabilitation of professional athletes faces objective difficulties associated with excessively intense loads and a short period between competitions. The use of plant adaptogens can improve the quality of the recovery process and reduce the time required for athletes to recover. The main purpose of the study was to review the use of adaptogens in sports; to analyze the dynamics of scientific publications over a 50-year period (1970-2024), and to determine the highest priority areas for their use in sports. The analysis was carried out using a bibliometric approach based on the PubMed / Scopus resources with the classification of outcomes by year, branch of science and individual adaptogens. The share of publications for the last 5 years was calculated as an indicator of the current research trend. An exponential trend of increasing the number of publications has been established, and over the past 5 years, their share has amounted to 28.3% of the number over a 50-year period. Despite the traditional popularity of Panax ginseng, other plant adaptogens have also recently shown an increase in publication activity, especially in studies of the adaptogenic properties of Rhodiola rosea (38.8% of publications over the last 5 years). The analysis of publications allowed us to classify the most promising directions of their use in sports. Various publications have noted effects such as increased athletic performance, normalization of stress hormones after competitions, acceleration of healing of injuries, stimulation of muscle mass gain, an antidepressant effect, as well as acclimatization during intercontinental flights and preparation for competitions in unfavourable conditions.